Perlindungan Hukum Paten Bagi Dosen Sebagai Inventor Dalam Hubungan Dinas Dengan Perguruan Tinggi Negeri Sebagai Instansi Pemerintah - Ledy Wila Yustino (Simbur Cahaya, 2019)
Patent rights regulate legal protection against the results of someone's intellectual thinking that produces technology. Patent protection is regulated in Act No. 13 of 2016 concerning Patents. The lecturer is identical to the results of the study so it is expected to encourage the registration of academic work to the Ministry of Law and Human Rights, so that the lecturers obtain legal intellectual property rights, on the other hand provide protection for the work of lecturers if their work is traced. Legal issues discussed in this thesis: How are significant legal constraints in patent legal protection against inventions produced by lecturers as inventors in official relations with state universities as government agencies? Research methods used in normative legal research contain empirical, normative legal research methods this empirical side concerning the implementation of normative legal provisions (laws) in its action in any particular legal event that occurs in a society. Patent is a form of protection of intellectual property rights, especially in terms of legal protection for lecturers as inventors in official relations with government agencies, Article 13 of the Patent Law and Ministerial Regulation No.72 / PMK.02 / 2015 have regulated it, the Patent Law and Ministerial Regulation as an implementing rule in which there are rules and sanctions in the event of a violation. Various existing constraints such as constraints of legal substance, institutions and legal culture affect law enforcement and patent legal protection, especially Article 13 of the Patent Law, implementing regulations are needed in the form of distribution of benefits that can support the creation of law enforcement. It is hoped that in the future a more complete and adequate implementing regulation can be formed to create legal protection for lecturers as inventors in official relations with universities as government agencies.